Eagle Voice Remembers : An Authentic Tale of the Old Sioux World - Neihardt, John G., 1881-1973 (Book collections on Project MUSE., 2021)
David C. Posthumus adds new clarity through his annotations, thus introducing John G. Neihardt's Eagle Voice Remembers to a new generation of readers and presenting a fresh understanding for fans of the original.